Benson Therapy in Gastritis Patients to Reduce Pain - Hamdani, Dadi; Sulistiani , Deana; Nurapandi, Adi (JURNAL KESEHATAN STIKes MUHAMMADIYAH CIAMIS, 2022)
Gastritis is an inflammation of the gastric mucosa caused by an irregular diet. Gastritis can be an emergency if not treated immediately, even in some conditions gastritis can also cause perforation to death. This study aims to obtain an overview of benson relaxation interventions to reduce pain in gastritis clients. The writing used uses a descriptive case study method through a nursing process approach that includes assessment, nursing diagnosis, planning, implementation and evaluation. With gastritis patient participants with acute pain problems in the Dahlia Room BLUD RSU Kota Banjar. Data collection through interviews, observation, physical examination, and documentation. Based on the results of the pain scale assessment, the results of the original scale reduction from 5 (0-10) to 2 (0-10) using the Numeric Rating Scale (NRS) measuring instrument method. The author found an effect after giving benson relaxation intervention on reducing pain intensity in gastritis patients and getting effective results, as evidenced by a decrease in the intensity of the pain scale. From the case study of benson relaxation intervention can be an alternative intervention that is done to gastritis patients so that there are no complications from the disease.